The Reinforcement Role of Nanoclays on the Mechanical Properties and Material Characterisation of Epoxy Composites - Dong, Yu; Mathew, Roney (Serials Publications, 2011)
Epoxy resins have shown outstanding material merits of low cost, ease of processing, fine adhesion to many substrates and good chemical resistance with a wide range of applications such as adhesives, construction materials and composite laminates. Nanofillers such as carbon nanotubes (CNTs), nanosilica and nanoclays possess the size effect with a large surface to volume ratio compared to conventional microfillers, to yield less material defects and increase particle/matrix interfacial area when subjected to well tailored composite properties. This study describes the use of two different shapes of nanoclays (i.e. tubular and platelet-like) to reinforce epoxy resin with different clay loadings from 1, 3, 5 to 8 wt% via mechanical mixing and ultrasonic treatment. The solution cast epoxy composite samples underwent flexural tests in three-point bending mechanism, scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis to correlate the morphological structure, clay dispersion with the resulting flexural properties. It was found that the flexural moduli of epoxy composites were moderately improved by the maximum value of 37% for 8 wt% platelet clay inclusions while a general downside trend of flexural strengths became manifested as opposed to that of neat epoxy. As expected, microsized clay agglomerates in an undispersed form deteriorate the functionalised mechanical performance of such epoxy composite system.